2006
DOI: 10.1163/156856206774879180
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline, an electroactive polymer, supports adhesion and proliferation of cardiac myoblasts

Abstract: Conductive polymers, such as polypyrrole, have recently been studied as potential surfaces/matrices for cell- and tissue-culture applications. We have investigated the adhesion and proliferation properties of H9c2 cardiac myoblasts on a conductive polyaniline substrate. Both the non-conductive emeraldine base (PANi) and its conductive salt (E-PANi) forms of polyaniline were found to be biocompatible, viz., allowing for cell attachment and proliferation and, in the case of E-PANi, maintaining electrical conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
183
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(194 citation statements)
references
References 12 publications
11
183
0
Order By: Relevance
“…In this way, adhesion and proliferation of cardiac myoblasts (H9c2) on conductive PANI substrates have been reported [98]. Both non-conductive emeraldine base and conductive salts forms of PANI were found to be biocompatible and to support cell attachment and proliferation, which attracted much attention of this material for tissue and biomedical applications.…”
Section: Electrically Active Materials For Tissue Engineeringmentioning
confidence: 94%
“…In this way, adhesion and proliferation of cardiac myoblasts (H9c2) on conductive PANI substrates have been reported [98]. Both non-conductive emeraldine base and conductive salts forms of PANI were found to be biocompatible and to support cell attachment and proliferation, which attracted much attention of this material for tissue and biomedical applications.…”
Section: Electrically Active Materials For Tissue Engineeringmentioning
confidence: 94%
“…Electrically stimulated random and aligned scaffolds enhanced the neurite length of DRGs by 83% and 47%, respectively, relative to unstimulated controls. Another electrically conductive polymer, polyaniline (PANI), has gained recent interest in tissue engineering applications [51][52][53]. Electrospinning a polymer blend of PANI with PCL/gelatin enhanced nerve stem cell proliferation and neurite outgrowth, when electrically stimulated [54].…”
Section: Electrically-active Electrospun Matsmentioning
confidence: 99%
“…[21][22][23][24][25] The use of PANi in engineering cell-laden three-dimensional biomimetic constructs has been limited due to its difficult and non-biocompatible processing steps and its insolubility in common solvents. [17,[26][27][28] Previously, we have reported that PANi can be integrated with synthetic PEGDA and naturally derived gelatin methacrylate (GelMA) hydrogels in situ in order to develop 3D conductive-hydrogels that are sufficiently biocompatible with seeded cells. [29,30] However, like studies similar to ours, the harsh processing methods were incompatible with cell encapsulation approaches.…”
Section: Introductionmentioning
confidence: 99%